The Role of Teacher Self-Efficacy in Special Education Teacher Candidates' Sensemaking: A Mixed-Methods Investigation. (June 2023) - Mathews, Hannah M.; Myers, Anna M.; Youngs, Peter A.
Shifts in special education over the last 25 years have increased the pressure on special education teacher preparation programs to improve the quality of opportunities to learn provided to teacher candidates. One aspect of quality that has not been extensively explored in the literature is the interaction between the individual candidate—the learner—and preparation experiences. Using survey and interview data from special education teacher candidates across six teacher preparation programs, we explore how candidates with differing levels of teacher self-efficacy (TSE) experience preparation. Findings suggest that TSE shaped how candidates made sense of preparation and what they took up from their opportunities to learn. Across phases, candidates with low- and high-TSE differed in how they reported on their learning opportunities and then how they interpreted these opportunities as shaping their future practice. We end with implications for research, policy, and practice in special education teacher preparation.